Paisajes culturales acuáticos del pacífico colombiano: memoria, patrimonio y arte de las comunidades afrodescendientes - Beltrán Chasqui, Jesica Wendy (2022)
The Aquatic Cultural Landscapes (ACL) in the Afro-descendant communities of the Colombian Pacific, is a study that is approached from the Cultural Geography, which aims to identify through religious, carnival and folkloric festivities of the Pacific carried out from north to south in different municipalities that make up the region, the diversity of cultural landscapes that remain present as a result of the African diaspora that remained in Colombia. In this way, the ACL category is proposed, which alludes to the close relationship that Afro-descendant communities have with the tropical rainforest, being water the element that stands out the most, such as high rainfall, the presence of rivers and the sea, which has shaped over time landscapes that evidence the presence of Afro-descendants in Colombia. These are examples of ways of life, of the fabric of social relations, of myths, legends, imaginaries and struggles to remain in their territory; in other words, they are evidence of the presence of human beings in the world. The ACL are a characteristic of the Afro-descendant people, which have been misinterpreted under arguments that generally catalog them as the environmental region or as the black region of Colombia, homogenizing what they really are, in other words, making invisible the existence of a landscape diversity, which is evidenced through the arts such as theater, dance and music, festive heritage and heritage education, which are subject to the conservation of memories and identities. Likewise, revealing the particularities of the landscape, therefore, its diversity, makes it possible to think of other forms of integration of the Pacific with the geo-body of the State, being pointed out from a governmental point of view as a marginal, poor and underdeveloped region in comparison with the rest of the country.